Vaccine-induced plasma IgA specific for the C1 region of the HIV-1 envelope blocks binding and effector function of IgG - Tomaras, Georgia D; Ferrari, Guido; Shen, Xiaoying; Alam, S Munir; Liao, Hua-Xin; Pollara, Justin; Bonsignori, Mattia; Moody, M Anthony; Fong, Youyi; Chen, Xi; Poling, Brigid; Nicholson, Cindo O; et al. (Proceedings of the National Academy of Sciences - PNAS, 2013)
Analysis of correlates of risk of infection in the RV144 HIV-1 vaccine efficacy trial demonstrated that plasma IgG against the HIV-1 envelope (Env) variable region 1 and 2 inversely correlated with risk, whereas HIV-1 Env-specific plasma IgA responses directly correlated with risk. In the secondary analysis, antibody-dependent cellular cytotoxicity (ADCC) was another inverse correlate of risk, but only in the presence of low plasma IgA Env-specific antibodies. Thus, we investigated the hypothesis that IgA could attenuate the protective effect of IgG responses through competition for the same Env binding sites. We report that Env-specific plasma IgA/IgG ratios are higher in infected than in uninfected vaccine recipients in RV144. Moreover, Env-specific IgA antibodies from RV144 vaccinees blocked the binding of ADCC-mediating mAb to HIV-1 Env glycoprotein 120 (gp120). An Env-specific monomeric IgA mAb isolated from an RV144 vaccinee also inhibited the ability of natural killer cells to kill HIV-1-infected CD4(+) T cells coated with RV144-induced IgG antibodies. We show that monomeric Env-specific IgA, as part of postvaccination polyclonal antibody response, may modulate vaccine-induced immunity by diminishing ADCC effector function.